The Effect of Compensation, Work Discipline, and Work Motivation on Performance (A Study of Brand X Mobile Coffee Riders in Surabaya) - Dini Aprilia Rismasari; Bowo Santoso (Journal of Economics and Management Scienties, 2026)
This research is motivated by the importance of human resource management in improving performance in partnership-based work systems, especially for Brand X mobile coffee riders in Surabaya. Therefore, this study aims to analyze several factors that can affect rider performance, such as compensation, work discipline, and work motivation. The population in this study includes all active Brand X riders, totaling 119 riders. The sampling method used is nonprobability sampling with purposive sampling technique. The research sample consists of 98 active riders who have worked for at least 1 month. The analysis method used in this study is Partial Least Square (PLS). The results of the study indicate that compensation have a positif and significant effect on rider performance, work discipline has a negative and insignificant effect on the performance, and work motivation have a positive and significant effect on rider performance of Brand X mobile coffee riders in Surabaya. These findings suggest that improving rider performance can be achieved more effectively through the implementation of a fair and proportionate compensation system that reflects rider’s actual working conditions, as well as through initiatives aimed at strengthening work motivation. In contrast, work discipline policies should be designed in accordance with the characteristics of a flexible partnership-based employment system.